Antillean manatee Trichechus manatus manatus (Sirenia: Trichechidae) as a motile ecosystem of epibiont fauna in the Caribbean Sea, Mexico - Violante-Huerta, Marco; Díaz-Gamboa, Raúl; Ordóñez-López, Uriel (THERYA, 2017)
The study of epibionts allows inferring ecological, biogeographic and health aspects of the host species (basibiont), and their study on marine mammals is scarce. The aim of this work was to characterize the epibiont fauna associated with the skin of captive individuals of the West Indian manatee in three sites from the Mexican Caribbean. In autumn 2014, 22 dorsal skin scrapings were collected from 11 captive manatees. The biological material was scraped off the skin with a blunt spatula, covering 100 cm2 of sampled area of the dorsal skin of each manatee. Samples were immediately fixed in 8 % formalin solution and placed in labeled vials for laboratory analysis. We used specialized literature to identify epibionts at the lowest taxonomic level possible. A total of 1,353 individuals from 31 taxa were found, belonging to eight phyla. Twenty nine taxa are new records of epibionts from Sirenians. The nematodes Monhystera sp. and Rabdolaimus sp., the adult and larvae of copepods from the Order Harpacticoida, the foraminifer Ammonia sp. and the rotifer Lecane sp. were the dominant epibionts. These new interactions may suggest that in the Caribbean Sea, the manatee skin represents a nutrient-rich substrate for an opportunistic fauna that is more diverse than previously estimated.